1986
DOI: 10.1111/j.1365-2141.1986.tb02930.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of transferrin with iron‐loaded rat peritoneal macrophages

Abstract: Rat peritoneal macrophages are capable, in vitro, of processing and releasing iron derived from phagocytosed, immunosensitized red cells. From 20% to 60% of the red cell iron can be returned to the culture medium in 24 h, with resident macrophages more active than inflammatory, peptone-induced macrophages. When apotransferrin is present in the culture medium, from 39% to 72% of iron released from macrophages is bound to the protein, with most of the remainder in a ferritin-like form. No distinct preference of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…It is likely that ferrocene initially gains access essentially to parenchymal and thereafter to reticuloendothelial cells where its iron is incorporated into ferritin and subsequently haemosiderin, which remains essentially within the cells. In contrast, iron dextran is probably taken up by macrophages, where its iron is stored only briefly before it is released to the circulation in the form of macrophage ferritin [27,281, which can furnish its iron to apotransferrin [27]. Some of the macrophage ferritin may also be taken up by ferritin receptors on hepatocytes [29], within which it is degraded in lysosomes and its iron is released and reincorporated into hepatocyte femtin [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that ferrocene initially gains access essentially to parenchymal and thereafter to reticuloendothelial cells where its iron is incorporated into ferritin and subsequently haemosiderin, which remains essentially within the cells. In contrast, iron dextran is probably taken up by macrophages, where its iron is stored only briefly before it is released to the circulation in the form of macrophage ferritin [27,281, which can furnish its iron to apotransferrin [27]. Some of the macrophage ferritin may also be taken up by ferritin receptors on hepatocytes [29], within which it is degraded in lysosomes and its iron is released and reincorporated into hepatocyte femtin [30].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the marked elevation of plasma Cp during the anemia of inflammation, when reticuloendothelial cell iron stores are elevated, remains paradoxical (15). The requirement for apotransferrin in macrophage iron release in vitro is also controversial; several investigators have shown a lack of stimulation by apotransferrin (16,17), whereas others have found a stimulatory effect (18). In fact, under some circumstances, Cp may enhance iron uptake by cells, possibly by a trivalent cation transporter on the cell surface (19 -21).…”
mentioning
confidence: 99%
“…The only possibility that this reaction could take place in vivo would be iron release from serum ferritin to transferrin. Saito et al [9] have observed release of iron in a ferritin-like form by cultured rat macrophage after ingestion of 59Fe-labelled erythrocytes. They have also found that much of the initial labelled iron was bound to apotransfer- [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although apotransferrin receptors have been found recently on rat macrophages [8], the presence of apotransferrin does not appear to be essential for the excretion of iron by these cells [9]. It thus appears that the inverse 'transferrin cycle' [10,11] would probably not be appropriate to explain the mechanism of intracellular iron mobilization.…”
Section: Introductionmentioning
confidence: 94%